Salivary Flow Alteration in Patients Undergoing Treatment for Schizophrenia: Disease-Drug-Target Gene/Protein Association Study for Side-effects - Anusa Arunachalam Mohandoss; Rooban Thavarajah (Journal of Oral Biology and Craniofacial Research)
Background: Salivary flow alteration (SA), is a known unwarranted effect of schizophrenic medications. It manifest either as reduced (xerostomia) or increased (sialorrhea) SA, among treated schizophrenic patients. It is believed that the SA is due to action of the drugs/disease process involving the muscarinic receptor-3 to process acetyl choline, the common neurotransmitter. The genetic mediation behind the SA in such patients remains largely unexplored. We aimed to address the same by using curated literary databases to identify such relationship, if any existed. Material and methods: Curated databases of Gene-Disease Association, www.DisGeNet.org and www.networkanalyst.ca were effectively used to identify the probable genes, strength of association and the drug-genes pathway that could be possibly be involved. The genes associated with schizophrenia and SA were analyzed in detail. Protein-Protein interaction (PPI) network proven experimentally in humans were used to identify the missing or unreported links. Results: In all 28 genes associated with schizophrenia were linked to SA. The genetic network of schizophrenia and xerostomia involved FGFR2 gene prominently and network module was statistically significant (P = 9.87*10−8) was achieved that had xerostomia as a node, while schizophrenia (P = 0.025) had statistical significance. Sialorrhea had no statistical significance (P = 0.555). When schizophrenia and sialorrhea connections were analyzed for genetic interaction, only gene GCH1 emerged. On combining the three disease entities, the association of TAC1 gene with sialorrhea was also identified. Using PPI, the coordination of CHRM3, TAC1 and GPRASP1 gene were identified. This network involved several genes that has significant influence on calcium signaling pathway (P = 7.74*10−16), cholingeric synapse(P = 6 × 10−4), salivary secretion(P = 4.38*10-3), endocytosis(P = 8.23*10−4), TGFβ signaling pathway(P = 0.0031), gap junction (P = 4.08*10-3) and glutamergic synapse(P = 6.4*10−3). The involvement of G-receptor signaling protein product, GNAQ was established. Discussion and conclusion: The possible genetic pathway of SA in schizophrenic patients are discussed in light of pharmacotherapeutics. Using the knowledge effectively would help to increase the quality of life of schizophrenic besides increasing the understanding to use saliva as a biomarker of prognosis of schizophrenia and its drug effects.